The importance of physical activity in obesity - Dobosiewicz, Anna Maria; Litwa, Ewelina; Różański, Gracjan; Badiuk, Nataliia (Journal of Education, Health and Sport, 2018)
Obesity is the result of an excessive supply of energy in relation to the body's needs. The etiological factors include environmental factors, genetic factors, sedentary lifestyle, avoiding physical activity, stress or eating excessive amounts of fat. It is estimated that the problem concerns almost 60 million Europeans. Obesity is associated with the possibility of many health complications, including hypertension, carbohydrate disorders, insulin resistance and cancers. Treatment of obesity is a long-term process that needs to be started by finding the main cause, by choosing the right diet, pharmacology, and psychotherapy for rehabilitation. The essence of the fight against obesity is physical activity, which in addition to reducing weight and improving the appearance of other results, such as: strengthening the osteoarticular system, improving the lipid profile, increasing efficiency and physical fitness and improving the mental state. Typical training used in the treatment of obesity are general exercises, characterized by medium or low intensity, effective use of oxygen by working muscles, mobilization of large muscle groups working alternately during exercise, cyclicity and the possibility of long-term exercise without breaks. The features of general fitness exercises include, among others: Nordic walking, walking, cycling, swimming and water exercises, aerobics, dancing and much more.